Соціально-економічна мотивація молоді: аспекти аналізу в контексті розвитку інноваційного потенціалу - Петіна, О. М.; Petina, O. (My University, 2016)
У статті розглянуто питання оцінки соціально-економічної мотивації розвитку інноваційного потенціалу молоді. Автором проаналізовано основні тенденції соціально-економічної мотивації розвитку інноваційного потенціалу української молоді. Запропоновано шляхи підвищення рівня мотивації молоді до розвитку інноваційного потенціалу. The article deals with the assessment of social and economy motivation of innovative potential of youth. The author interpretation of social and economy motivation of development of youth innovative potential is offered. The innovative potential of youth as a determinant of becoming a knowledge economy is investigated.
Social and economy motivation of youth: analysis aspects in the development of innovative potential
Keywords: мотивація; молодь; соціально-економічна мотивація; інноваційний потенціал; соціально-економічна мотивація розвитку інноваційного потенціалу молоді; motivation; youth; social and economy motivation; innovation potential; social and economy motivation of development innovative potential of youth